Building Purposeful Superintendent and School Board Relationships Through Examining the Historical Narrative of Evolving Roles - Henrikson , Robin L. (International Dialogues on Education Journal, 2019)
The author presents a summary of the changing role of the traditional superintendent within the United States through the lens of how this work can be challenged or encouraged by the relationship with her or his respective board. The author emphasizes how the evolving roles of both the superintendent and school board member have contributed to the lack of clarity around their respective responsibilities that has influenced relational factors between these two groups. The importance of building, nurturing and sustaining relationships between the superintendent and school board in order to be proactive and prepared to encounter the many issues that school districts face daily is integral to this conversation. School boards and superintendents must understand how to collaborate beyond simply abiding by their delegated role at the time to flourish and support a successful school district.